The interaction of orthography, phonology and semantics in the process of second language learners’ Chinese character production - Zhang, Linlin; Xing, Hongbing (Frontiers in Psychology, 2023)
Theories of connectionism emphasize the mappings of orthography, phonology, and semantics in the process of word recognition and production. Chinese has a logographic writing system, which is markedly different from alphabetic languages. The current study investigated how orthography, phonology, and semantics contribute to Chinese character production among Chinese as a second language (CSL) learners. This study collected 33,856 Chinese characters in a sample of 2,116 CSL learners with 7 diverse L1s. ANOVA was conducted to examine the effect of Chinese character error type on 7 L1s and three Chinese proficiency levels. The results of ANOVA revealed that successful CSL learners’ Chinese character production was derived from connections between orthography, semantics, and phonology. Semantics, especially the orthography-semantics connection, was the key point for production skills. Furthermore, connectionist models of languages rather than language distance affected production. These findings indicate that Chinese character production is associated with not only orthographic knowledge but also representation mechanisms of orthography, phonology, and semantics between different language writing systems. The results contribute to a better understanding of literacy skills in CSL learners. Future research could further address how CSL learners transform perceptive skills into production skills and the correlation between reading and writing skills by examining and controlling other important cognitive variables.